(untitled) (Research, Society and Development, 2021)
This article empirically assesses effects on education in Brazil. The study addresses the issue with panel data in fixed effect and random effect by units of the federation in the period 2002-2014. Using other explanatory variables, the impact of spending on sport and leisure on education is discussed. Based on the two different panel models, the results support the hypothesis that increases in spending on sport and leisure produce increases in the years of study. The variables that represent expenditure on health and sanitation, access to drinking water, access to adequate sewage installation, school attendance and income inequality are also statistically significant in the study and confirm the expected signs.